2014
DOI: 10.1021/ol502174n
|View full text |Cite
|
Sign up to set email alerts
|

Mild Copper–TBAF-CatalyzedN-Arylation of Sulfoximines with Aryl Siloxanes

Abstract: An efficient copper-TBAF-catalyzed C-N bond formation of sulfoximines with arylsiloxanes in dichloromethane at room temperature, affording the desired N-aryl sulfoximines in good to excellent yields under an oxygen atmosphere, is reported. This method complements the existing synthetic approaches due to some advantageous properties of arylsiloxanes such as availability, low toxicity, ease of handling, high stability, and environmental benignity under mild reaction conditions, thus opening a new approach to pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…[16] Several methodologies for the N-arylation of NH-sulfoximines have been reported in the last decade. In particular, this N-functionalization can be achieved using different arylating agents as aryl halides, [123] aryl triflates, [124] aryl boronic acids, [125] aryl siloxanes, [126] diaryl iodonium salts, [127] and arynes. [128] An and Zhang reported a general method for the N-arylation of NHsulfoximines using sodium arylsulfinates as efficient arylating agent.…”
Section: N-arylationmentioning
confidence: 99%
“…[16] Several methodologies for the N-arylation of NH-sulfoximines have been reported in the last decade. In particular, this N-functionalization can be achieved using different arylating agents as aryl halides, [123] aryl triflates, [124] aryl boronic acids, [125] aryl siloxanes, [126] diaryl iodonium salts, [127] and arynes. [128] An and Zhang reported a general method for the N-arylation of NHsulfoximines using sodium arylsulfinates as efficient arylating agent.…”
Section: N-arylationmentioning
confidence: 99%
“…reported that N‐arylsulfoximines exhibited interesting physicochemical properties and in vitro characteristics [6] of great significance for drug development. Many N‐arylation substrates for NH‐sulfoximines have been identified, with examples of such substrates including aryl halides, [56] arylboronic acids, [57,58] aryl sulfonates, [59] arylsiloxanes, [60] aromatics, [65] aryl iodonium salts, [61] and others [62,63]…”
Section: Transformations Of Sulfoximinesmentioning
confidence: 99%
“…Lee et al. in 2014 reported efficient copper/TBAF‐catalyzed C−N bond cross‐couplings of sulfoximines and arylsiloxanes at room temperature under oxygen atmosphere to provide the desired N‐arylsulfoximines in good yields [60] . These reactions and their arylsiloxanes serving as arylation reagents were indicated by the authors to have some advantageous properties such as low toxicity, ease of handling, high stability, environmental friendliness, and mild reaction conditions (Scheme 34), [60] but arylsiloxanes are the downstream products of aryl halides, and thus more expensive and display much lower atom economy.…”
Section: Transformations Of Sulfoximinesmentioning
confidence: 99%
“…In an ensuing precedent, Lee et al improvised the earlier reported strategy and successfully accomplished the CÀ N bond formation of sulfoximines with low toxic arylsiloxanes under amiable conditions (Scheme 7). [21] The reactions performed at room temperature by using CuI (10 mol %) and TBAF (10 mol %) as the catalysts and under balloon pressure of O 2 , allowed in accessing to desired N-aryl sulfoximine products. Moderate to excellent yields (66-82%) were accommodated when various substituted arylsiloxane reacted with S-phenyl-S-methyl sulfoximine.…”
Section: Transition Metal Catalyzed and Metal-free Approachmentioning
confidence: 99%